2017
DOI: 10.1557/adv.2017.407
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Tin Oxide and Zinc Magnesium Oxide Prepared by Hollow Cathode Sputtering for CdTe Photovoltaics

Abstract: This work reports the fabrication and characterization of superstrate-type Zn1-xMgxO/CdTe heterojunction solar cells on both CdxSnyO and commercial SnO2:F transparent conducting oxides (TCOs) in which the ZMO and CTO layers are produced for the first time by hollow cathode sputtering. The sputtering is conducted in a reactive mode using metal or alloyed metal targets fitted to a custom-made linear cathode. It is notable that the CdS buffer layer conventionally employed in CdTe solar cells is entirely replaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In 2017, Delahoy et al reported the fabrication of ZMO/CdTe solar cells, but the devices showed unsatisfactory efficiencies (∼10.5%) accompanied by low fill factors (FF) due to the existence of an S-kink in the current density−voltage (J−V) curves. 11 In 2018, Bittau et al reported ZMO/CdTe solar cells, but their best-performing cell showed an efficiency of 13.5% with a low FF around 65%. 12 S-kink in J−V curves has been observed in other solar cells including organic, 14 copper indium gallium selenide (CIGS, without blue photons), 15 and crystalline silicon 16 cells.…”
Section: ■ Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2017, Delahoy et al reported the fabrication of ZMO/CdTe solar cells, but the devices showed unsatisfactory efficiencies (∼10.5%) accompanied by low fill factors (FF) due to the existence of an S-kink in the current density−voltage (J−V) curves. 11 In 2018, Bittau et al reported ZMO/CdTe solar cells, but their best-performing cell showed an efficiency of 13.5% with a low FF around 65%. 12 S-kink in J−V curves has been observed in other solar cells including organic, 14 copper indium gallium selenide (CIGS, without blue photons), 15 and crystalline silicon 16 cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…15−17 For ZMO/CdTe solar cells, it is generally attributed to the high CBO spike at the ZMO/ CdTe interface. 11,18 Device modeling has shown that a high CBO spike, large interface recombination velocity, and low doping density in absorber and buffer layers can induce a significant barrier at the ZMO/CdTe interface that blocks electrons transferring from CdTe into fluorine doped tin oxide (FTO) electrode, causing the S-kink in the J−V curves. 6 However, keeping the CBO spike small and fully realizing the benefits of the CBO spike are challenging.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations